Cataract in childhood diabetes: more than what meets the eye - Syal, Simran; Goel, Anil K.; Jagzape, Tushar B.; Khan, Lubna; Jaiswal, Mohit D.; Gandhoke, Charandeep Singh (International Journal of Contemporary Pediatrics, 2025)
Diabetic cataract is a rare but sight threatening complication in children. Two cases of paediatric diabetic cataract are described, one is in a six-year-old girl with diabetes duration of four years with systemic features of poorly controlled T1DM in the form of Mauriac syndrome and another is of a 13 years 6 months old boy with relatively recent diabetes diagnosis 6 months back, both presenting with visually significant cataracts. Regular ophthalmological screening examinations in patients with T1DM starting right from the time of diagnosis are essential to pick up and treat this complication early for best results.